A Comparison of the Educational Methods of Zoltán Kodály and his Student, Klára Kokas - Székely, Csilla Imola (Central European Journal of Educational Research, 2021)
After the presentation of Klára Kokas’ pedagogical methods and her own invented musical activities with children, I shall try to compare these methods with Zoltán Kodály’s music educational practices and innovations to emphasize the continuity and discontinuity of Hungarian music educational practice. Kokas centered her pedagogical concept on children’s creativity, human relations, acceptance of and complete attention paid to others. This world view and ideology was constructed around a child-centered sensitivity, music being her primary pedagogical resource. The goal of this paper is to explore the main elements and characteristics of Klára Kokas’s pedagogy, which were revolutionary and new in the fields of personality development, music and complex art education. I will draw out those elements, which show similarity between his work and Kokas’s, then I will point out those components in which Kokas offered excess for personality development. The main elements of this concept is music, dance improvisation, motions, imaginative stories, visual arts, painting and drawing, but it’s most important component is that very specific and intimate relation, which connected her to the children. My purpose is to highlight the contours of the Kokas’ pedagogy. In my comparative research I mention the reform pedagogical elements of the Zoltán Kodály’s concept, and I seek the common and different elements of their music educational ideas and innovations. The importance of her beliefs and moral convictions in the art of education will be outlined then.